Trigonometry! #131

Geometry Level 3

If sin x + sin y = 3 ( cos y cos x ) \sin x + \sin y = \sqrt{3}(\cos y-\cos x) then find the value of sin 3 y + sin 3 x \sin 3y + \sin 3x .

This problem is part of the set Trigonometry .


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

The equation can be rewritten as

sin ( x ) + 3 cos ( x ) = sin ( y ) + 3 cos ( y ) \sin(x) + \sqrt{3}\cos(x) = -\sin(y) + \sqrt{3}\cos(y)

1 2 sin ( x ) + 3 2 cos ( x ) = 1 2 sin ( y ) + 3 2 cos ( y ) \Longrightarrow \dfrac{1}{2}\sin(x) + \dfrac{\sqrt{3}}{2}\cos(x) = -\dfrac{1}{2}\sin(y) + \dfrac{\sqrt{3}}{2}\cos(y)

cos ( π 3 ) sin ( x ) + sin ( π 3 ) cos ( x ) = cos ( 2 π 3 ) sin ( y ) + sin ( 2 π 3 ) cos ( y ) \Longrightarrow \cos(\dfrac{\pi}{3})\sin(x) + \sin(\dfrac{\pi}{3})\cos(x) = \cos(\dfrac{2\pi}{3})\sin(y) + \sin(\dfrac{2\pi}{3})\cos(y)

sin ( x + π 3 ) = sin ( y + 2 π 3 ) \Longrightarrow \sin(x + \dfrac{\pi}{3}) = \sin(y + \dfrac{2\pi}{3}) ,

and so either

(i) x + π 3 = y + 2 π 3 + 2 n π x = y + π 3 + 2 n π x + \dfrac{\pi}{3} = y + \dfrac{2\pi}{3} + 2n\pi \Longrightarrow x = y + \dfrac{\pi}{3} + 2n\pi for any integer n , n, or

(ii) x + π 3 = π ( y + 2 π 3 ) + 2 n π x = y + 2 n π x + \dfrac{\pi}{3} = \pi - (y + \dfrac{2\pi}{3}) + 2n\pi \Longrightarrow x = -y + 2n\pi for any integer n n .

In case (i) we would then have sin ( 3 x ) = sin ( 3 y + π + 6 n π ) = sin ( 3 y ) \sin(3x) = \sin(3y + \pi + 6n\pi) = -\sin(3y) , and in case (ii) we would then have sin ( 3 x ) = sin ( 3 y + 6 n π ) = sin ( 3 y ) \sin(3x) = \sin(-3y + 6n\pi) = -\sin(3y) , and thus in either case we find that

sin ( 3 y ) + sin ( 3 x ) = sin ( 3 y ) sin ( 3 y ) = 0 . \sin(3y) + \sin(3x) = \sin(3y) - \sin(3y) = \boxed{0}.

Marvin Chong
Feb 18, 2020

A Solution That Got Lucky A Solution That Got Lucky

An Alternative Solution To \(x=-y\) An Alternative Solution To x = y x=-y

Edit: A little correction to the second image. The solution is true if x = y x=-y .

Just by looking the expression, if angles x=y=0 or n(pi) then cos(x)=cos(y)=1 and since cos(x) is subtracted from cos(y) the equation balance 0=0

Yes, that is a good shortcut. But the issue would then be if this is the case for all possible x , y x,y that satisfy the given equation, hence my more formal approach.

Looking at your solution, though, made me realize that I did not cover one of the possible general cases for the relationship between x x and y y , so I have edited my solution to rectify this initial oversight.

Brian Charlesworth - 6 years, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...